Click chemistry at the microscale. Issue 5 (11th January 2019) - Hong, Tingting; Liu, Wenfang; Li, Ming; Chen, Chuanpin
Abstract : This manuscript reviews recent developments in click chemistry in microscale systems. Abstract : Click chemistry has attracted tremendous attention for the fabrication of novel microscale systems based on its high reaction efficiency, satisfactory versatility and simple processing. Meanwhile, microscale systems also provide desirable analytical platforms for click reaction study. Herein, we review the employment of click reactions for developing state-of-the-art microchip-based and capillary-based systems. The advantages of innovative off-stoichiometry thiol–ene (OSTE)-microchips, bio-functionalized microchips and monolithic microsystems for chemical and biological assays are highlighted. Moreover, the potential of microscale systems applied for click reaction investigation is indicated as well. This article presents an overview of the recent developments in the combination of microscale systems and click chemistry.